DGCR2 targeting affibody molecules for delivery of drugs and imaging reagents to human beta cells - Pierre Cheung; Jonas Persson; Bo Zhang; Svitlana Vasylovska; Joey Lau; Sofie Invast; Olle Korsgren; Stefan Ståhl; John Löfblom; Olof Eriksson (Scientific Reports)
Abstract A distinctive feature of both type 1 and type 2 diabetes is the waning of insulin-secreting beta cells in the pancreas. New methods for direct and specific targeting of the beta cells could provide platforms for delivery of pharmaceutical reagents. Imaging techniques such as Positron Emission Tomography (PET) rely on the efficient and specific delivery of imaging reagents, and could greatly improve our understanding of diabetes etiology as well as providing biomarkers for viable beta-cell mass in tissue, in both pancreas and in islet grafts. The DiGeorge Syndrome Critical Region Gene 2 (DGCR2) protein has been suggested as a beta-cell specific protein in the pancreas, but so far there has been a lack of available high-affinity binders suitable for targeted drug delivery or molecular imaging. Affibody molecules belong to a class of small affinity proteins with excellent properties for molecular imaging. Here, we further validate the presence of DGCR2 in pancreatic and stem cell (SC)-derived beta cells, and then describe the generation and selection of several Affibody molecules candidates that target human DGCR2. Using an in-house developed directed evolution method, new DGCR2-binding Affibody molecules were generated and evaluated for thermal stability and affinity. The Affibody molecules variants were further developed as targeting agents for delivering imaging reagents to beta cell. The Affibody molecule ZDGCR2:AM106 displayed nanomolar affinity, suitable stability and biodistribution, with negligible toxicity to islets, qualifying it as a suitable lead candidate for further development as a tool for specific delivery of drugs and imaging reagents to beta cells.